TheDescription of Teachers’Strategy to Teach Reading Comprehension at SMP Negeri 1 Lahewa Timur in 2022/2023 - Yayuk Fadmawati Zebua; Kristof Martin Efori Telaumbanua; Trisman Harefa; Adieli Laoli (Edumaspul: Jurnal Pendidikan, 2023)
Reading is one process of getting information from the writer to the reader. In the reading context the basic purpose is the reader can understand the text. In this research, researchers found some problem there are the students do not understand which is the main idea and the students can’t conclude the content of the text. Related to these problems, the purpose of this research is to describe the teachers’ strategy to teach reading comprehension in classroom. To make it clear the researcher use qualitative research especially descriptive research is to describe a phenomenom and its characteristics. The more importantly the result of this research is the teacher at SMP Negeri 1 Lahewa Timur use Small Group discussion and Listen, Read and Discuss. As recommendation the strategy in teaching reading comprehension is better to used Small group discussion and Listen read and discuss in other school . Furthermore, the researcher expects the next researchers to conduct the same research to find out more the teachers’ strategy to teach reading comprehension in the future by making this research as the reference in the same field